Drug-resistant Tuberculosis in Pediatric: A Case Report - Lubis, Halisyah Hasyim; Daulay, Rini Savitri (Asian Australasian Neuro and Health Science Journal (AANHS-J), 2023)
Introduction: Drug-resistant tuberculosis (DR TB) is a condition where Mycobacterium tuberculosis is resistant to isoniazid, rifampicin or resistant to isoniazid and rifampin as well as other first-line anti-tuberculosis drugs (OAT). Tuberculosis (TB) is a contagious infectious disease, caused by Mycobacterium tuberculosis germs where the source of transmission is through droplets containing TB germs. Case Report: A 10 years 7 months girl, came to the MDR Polyclinic at the Haji Adam Malik Medan Central General Hospital (RSUP HAM Medan) on March 21 2023 bringing the results of the TB Molecular Rapid Test (TCM-TB) examination from the Teladan Barat Health Center with Rifampicin results were resistant and on March 24 2023 the patient was hospitalized. Currently, the patient is complaining of a cough that has been experiencing for ± 3 weeks. Cough with the impression of a dry cough and is continuous so that it interferes with daily activities. The cough does not improve even though the patient has taken cough medicine. There is no fever, there is also no history of previous fever. According to the anamnesis from the patient’s parents, there has been a weight loss in the last 2 months, around ± 4 kg. There is no family history of long-term cough, but according to parents, there is a neighbor of the patient who suffers from pulmonary TB and is undergoing treatment. Discussion: After the diagnosis of drug-resistant tuberculosis is confirmed, an evaluation is carried out whether the patient meets the criteria for drug-resistant TB treatment guided by short-term or long-term oral drug-resistant tuberculosis. Patients who meet the evaluation criteria for treatment can immediately be given short-term oral drug-resistant tuberculosis therapy. If the patient does not meet the criteria for short-term treatment, long-term drug-resistant tuberculosis treatment is given. Routine evaluations are carried out during treatment and when the results of drug sensitivity tests are available, treatment is adjusted according to the examination results. Conclusion: A case of drug-resistant tuberculosis in a girl aged 10 years 7 months has been reported which was diagnosed based on anamnesis, physical examination, and supporting examinations, there was also a history of close contact with TB sufferers, and the results of TCM examination of sputum fluid showed rifampicin resistant MTB growth. Patients are treated as drug-resistant TB cases with a short-term regimen with regular monitoring of treatment response and side effects.